Validation of the Malay version of the p-QOL questionnaire - Dasrilsyah, Rima Aggrena; Beng, Kwang Ng; Atan, Ixora Kamisan; Khong, Su Yen; Nusee, Zalina; Lim, Pei Shan (Springer, 2020)
Introduction This study aimed to translate and validate the P-QOL questionnaire in the Malay language. Methods The P-QOL questionnaire was translated into the Malay language and subsequently back-translated to English. Testretest reliability and internal consistency were tested. All patients who visited the gynecology outpatient clinic of UKMMC, UMMC and IIUM between January 2016 and May 2017 completed the P-QOL questionnaires and were assessed for POP-Q staging. Results One hundred twenty patients with symptomatic pelvic organ prolapse and 180 asymptomatic patients were included. The Cronbach’s alpha for each domain was > 0.70, which confirmed that there was a highly acceptable internal consistency. The value varied between 0.88 (role limitation) and 0.912 (sleep/energy). Test-retest reliability showed a significant correlation between the total scores for each domain (p < 0.001). There was a significant correlation between P-QOL domain scores and vaginal examination findings (POP-Q). With a higher POP-Q stage, a higher impact on the quality of life was detected in symptomatic patients. The total scores from all domains were significantly higher in symptomatic patients. Conclusion The Malay translated version of the P-QOL questionnaire is a reliable, consistent, and valid instrument for assessing the severity of the symptoms and impact on the quality of life among women with uterovaginal prolapse. It is easily understood, administered, and self-completed by patients